The Moderating Role of Individual Adaptability Towards the Influence of Transformational Leadership and Employee Reactions on Individual Work Performance in Malaysia Oil and Gas Company - Albert, Apoi (International Journal of Academic Research in Business and Social Sciences, 2021)
Leadership effectiveness has been the subject of interest by researchers over the years. Labour market is changing very quickly and working domain constantly modified due to uncertain social and economic environment. This development requires individual to adapt fast in an increasingly complex work environment which demands employees to apply creative, innovative, collaborative, and analytical skills that technology cannot replicate. Such skills can generate new ideas, products, and better procedures. Hence, this study aims to propose a leadership effectiveness model that incorporates individual adaptability as a moderating factor. To elucidate and expand the current leadership effectiveness model, the expectancy theory of motivation was applied in this study to explore the thought process of interaction between individuals and the environment. The respondents constitute employees of oil and gas companies in the upstream segment in East and West Malaysia. This study employed a cross-sectional research design and data were obtained using a multistage sampling technique from 204 employees at four hierarchical positions. The Structural Equation Modelling (SEM) in IBM-SPSS-AMOS 24.0 was utilized to analyze and assess the inter-relationships of constructs. All four hypotheses achieved the desired significant level and were supported. The findings stress the significance of individual adaptability in boosting work performance, especially since there is scarce research on individual adaptability that examines skills such as creative, innovative, collaborative, and analytical skills but rather on culture and unfamiliar environment. The limitations and recommendations are also highlighted in this study.